Written Journalism and Language Culture - Junková, Bohumila (Stylistyka, 2006)
The paper aims to point out some instances of language innovations appearing in written journalism and to comment on their contribution to the culture of present-day language. The data were obtained from the following Czech dailies published between 2000 and 2005: “Mlada fronta DNES”, “Právo”, and “Lidové noviny”. As written journalistic texts rank among official types of communication, the logical expectation would be for them to employ strictly standard language, with moderately literary ways of expression. However, in practice this is very different. Contemporary journalism is open to language means (mostly lexical) from different stylistic levels. Many of these never establish themselves as permanent components of language. This is especially fortunate in the case of inadequately used, strongly peiorative expressions, which can hardly be considered a positive contribution to language culture.